Early and Late Outcomes of Cardiovascular Surgery in Patients With Ehlers-Danlos Syndrome. Issue 6 (November 2021) - Elsisy, Mohamed F.; Pochettino, Alberto; Dearani, Joseph A.; Bower, Thomas C.; McBane, Robert D.; Graham, Gabriel C.; Deyle, David R.; Bonnichsen, Crystal R.; Stephens, Elizabeth H.
Background: Cardiovascular surgical outcomes reports are few for vascular type IV of Ehlers- Danlos Syndrome (vEDS) compared to non-vascular types I-III (nEDS). Methods: To define cardiovascular surgical outcomes among adult patients (≥18 years) with EDS types, a review of our institution's in-house STS Adult Cardiac Surgery Database-compliant software and electronic medical records from Mayo Clinic (1993–2019) was performed. Outcomes were compared for vEDS patients and nEDS patients. Demographics, baseline characteristics, operative, in-hospital complications and follow-up vital status were analyzed. Results: Over the study time frame, 48 EDS patients underwent surgery (mean age 52.6 ± 14.6 years; 48% females). Of these, 17 patients had vEDS and 31 patients had nEDS. Six patients (12.5%) underwent prior sternotomy. Urgent or emergent surgery was performed in 10 patients (20.8%). Aortic (vEDS 76.5% vs. nEDS 16.1%) and mitral procedures (vEDS 11.8% vs. nEDS 48.4%) were the two most common cardiovascular surgeries performed (p < .01 and p = .007, respectively). Cardiopulmonary bypass time (CPB) (165 ± 18 vs. 90 ± 13 min; p = .015) and aortic cross clamp times (140 ± 14 vs. 62 ± 10 min; p < .001) were longer for vEDS patients. There was 1 (2.1%) early and 7 (14.6%) late deaths; 6 among vEDS and 2 among nEDS patients. Survival at 5 (80% vs. 93%), 10 (45% vs. 84%) and 15 years (45% vs. 84%) was lower in patients with vEDS (p = .015 for each comparison). Conclusion: Cardiovascular surgeries are significantly more complex with longer bypass and cross clamp times for type IV vEDS compared to nEDS patients. Reduced overall survival underscores the complexity and fragility of vEDS patients.